Romantic poetry and literary coteries : the dialect of the tribe - Fulford, Tim, 1962- (New York, NY : Palgrave Macmillan, 2015)
"How does Romantic poetry read if seen as the product of social authorship--the group language of coteries of writers, editors, publishers and critics--rather than as a series of verbal icons--original lyrics and romances composed by individual geniuses? Romantic Poetry and Literary Coteries explores Romanticism as a discourse characterized by tropes and forms that were jointly produced by literary circles - writing communities - in self-conscious opposition to prevailing social and political values and in deliberate differentiation from the normal practices of contemporary print culture. Among the tropes examined are allusion and borrowing; among the forms discussed are blank-verse effusions, political squibs, magazine essays, millenarian prophecies, long-form notebook verse, illustrated tour poems and prose journals. Coteries considered include the Southey/Coleridge circle, including Bowles, Cottle, Cowper, Lamb, Lloyd, Robinson and Wordsworth; the Bloomfield circle, including Capel Lofft and Thomas Hood; the Clare circle, including Byron, Cowper, William Knight and John Taylor; the Cockneys, including Richard Brothers, William Bryan, De Quincey, Hood, Leigh Hunt, Robert Mudie, Patmore"--
Introduction -- PART I: "A SECT OF POETS": THE DIALECT OF FRIENDSHIP IN SOUTHEY, COLERIDGE, AND THEIR CIRCLES. 1. The Politicization of Allusion in Early Romanticism: Mary Robinson and the Bristol Poets; 2. Brothers in Lore: Fraternity and Priority in Thalaba, "Christabel, " and "Kubla Khan"; 3. Signifying Nothing: Coleridge's Visions of 1816 -- Anti-Allusion and the Poetic Fragment; 4. Positioning The Missionary: Poetic Circles and the Development of Colonial Romance -- PART II: THE "RURAL TRIBE": LABORING CLASS POETS AND THE TRADITION. 5. The Production of a Poet: Robert Bloomfield, his Patrons, and his Publishers; 6. Iamb yet what Iamb: Allusion and Delusion in John Clare's Asylum Poems -- PART III: THE LINGO OF LONDONERS: THE "COCKNEY SCHOOL". 7. Romanticism Lite: Talking, Walking and Name-Dropping in the Cockney Essay; 8. Allusions of Grandeur: Prophetic Authority and the Romantic City.
Includes bibliographical references and index.
Keywords: English poetry -- 19th century -- History and criticism; Romanticism -- England; Literature and society -- England -- History -- 19th century; Poets, English -- 19th century; English poetry; Literature and society; Poets, English; Romanticism; England; 1800-1899; Criticism, interpretation, etc; History